Association Between Social Networks and Subjective Well-Being in Adolescents: A Systematic Review. Issue 2 (March 2021) - Webster, Deborah; Dunne, Laura; Hunter, Ruth
Social networks are ubiquitous in the lives of adolescents. This work systematically reviewed all studies which investigated the relationship between subjective well-being and the social networks of adolescents. Twenty-nine articles (out of 1, 204 hits) were included within the review. Offline social networks have a positive association between the mood, self-esteem, and loneliness of adolescents but not body image. Nine of the studies investigating online social networks found a positive association on mood, life satisfaction, and loneliness through support seeking and receiving positive feedback. Fifteen of the studies found a negative association between online social networks and mood, self-esteem, life satisfaction, body image, and overall subjective well-being through high investment, passive use, receiving negative feedback, and social media ostracism. There is a need for intervention programs and education for young people, educators, and parents to address the risks to subjective well-being brought about by online social networks.